The Provision of Social Support Increases the Return-to-Work Rate of Musculoskeletal Injury Patients: A Systematic Review - Arfiani, Siti Zahra; Muhammad Hasan; Kusumastuti, Inke (Indonesian Journal Publisher, 2025)
The most common problem in orthopedics that becomes the main cause of disability worldwide is musculoskeletal injuries. It may develop into chronic conditions that interfere with social function, quality of life, and productivity. The Return to Work (RTW) Rate is used for measuring the success of intervention. Provision of social support becomes the psychosocial interventions that may reduce the negative impact. This study aimed to learn whether social support may increase the RTW rate of musculoskeletal injury, by conducting a systematic review based on Preferred Reporting Items for System and Meta Analysis (PRISMA). Literature search using three databases, Springer, PubMed, ScienceDirect, and manual searching. The critical appraisal tool used was the Joanna Briggs Institute (JBI) checklist. There were seven included articles with high and medium quality. All studies were conducted in developed countries. Social support from supervisors and colleagues increases the chances of achieving partial and sustained RTW, and reduces the rate of interrupted RTW, while social support from family and friends can reduce the chances of achieving a partial RTW. More studies analyzing provision of social support to patients with other medical conditions should be made in the population of working age in developing countries, to assess for possible generalization of the results of the present systematic review.